Persistent Circulation of Enterohemorrhagic Escherichia coli (EHEC) O157:H7 in Cattle Farms: Characterization of Enterohemorrhagic Escherichia coli O157:H7 Strains and Fecal Microbial Communities of Bovine Shedders and Non-shedders - Bibbal, Delphine; Ruiz, Philippe; Sapountzis, Panagiotis; Mazuy-Cruchaudet, Christine; Loukiadis, Estelle; Auvray, Frédéric; Forano, Evelyne; Brugère, Hubert (Frontiers in Veterinary Science, 2022)
Cattle are carriers, without clinical manifestations, of enterohemorrhagic Escherichia coli (EHEC) O157:H7 responsible for life-threatening infections in humans. A better identification of factors playing a role in maintaining persistence of such strains in cattle is required to develop more effective control measures. Hence, we conducted a study to identify farms with a persistent circulation of EHEC O157:H7. The EHEC O157:H7 herd status of 13 farms, which had previously provided bovine EHEC O157:H7 carriers at slaughter was investigated. Two farms were still housing positive young bulls, and this was true over a 1-year period. Only one fecal sample could be considered from a supershedder, and 60% of the carriers shed concentrations below 10 MPN/g. Moreover, EHEC O157:H7 represented minor subpopulations of E. coli. PFGE analysis of the EHEC O157:H7 strains showed that persistent circulation was due either to the persistence of a few predominant strains or to the repeated exposure of cattle to various strains. Finally, we compared fecal microbial communities of shedders (S) (n = 24) and non-shedders (NS) (n = 28), including 43 young bulls and nine cows, from one farm. Regarding alpha diversity, no significant difference between S vs. NS young bulls (n = 43) was observed. At the genus level, we identified 10 amplicon sequence variant (ASV) indicators of the S or NS groups. The bacterial indicators of S belonged to the family XIII UCG-001, Slackia, and Campylobacter genera, and Ruminococcaceae NK4A21A, Lachnospiraceae-UGC-010, and Lachnospiraceae-GCA-900066575 groups. The NS group indicator ASVs were affiliated to Pirellulaceae-1088-a5 gut group, Anaerovibrio, Victivallis, and Sellimonas genera. In conclusion, the characteristics enhancing the persistence of some predominant strains observed here should be explored further, and studies focused on mechanisms of competition among E. coli strains are also needed.